SIGNIFIKANSI IBADAH SHOLAT DALAM PEMBENTUKAN KESEHATAN JASMANI DAN ROHANI - Sazali . (Universitas Nasional, 2016)
Islam advice that Sholat be performed in ritually clean environment. When worshipping, the clothes that are worn and the place of player mus be clean. Both men and women are required yo cover their bodies (aurah) in reasonably loose-fitting garments. The well known adage or hadis by Al Nawawi that purity is half the faith illustrates how Islam has incorporated and modified existing rules of purity in its religious system. Sholat is one of the five pillars in the faith of Islam and obligatory religious duty for every muslim. It is physical, mental and spiritual act of worship that is observed five times every day at prescribed times. Every movement in the sholat is accompanied by the takbir except the standing between the ruku” and sujud and the ending which has a derivation of the muslim greeting asalamu alaikum”. Muslims believe that prophets Allah offered daily prayers and were humble in submission to the Oneness of Allah. Muslim also believe that the main duty of the prophets of Allah is to teach mankind to humbly submit themselves to Oneness of Allah. Sholat is cited as a means of restraining a believer from social wrong and moral deviancy.